2014
DOI: 10.1371/journal.pone.0115411
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Molecular Characterization of Microneme 5 of Eimeria acervulina

Abstract: In the present study, the microneme 5 gene of Eimeria acervulina (E. acervulina) (EaMIC5) was cloned and characterized. Specific primers for the rapid amplification of cDNA ends (RACE) were designed based on the expressed sequence tag (EST, GenBank Accession No. EH386430.1) to amplify the 3′- and 5′-ends of EaMIC5. The full length cDNA of this gene was obtained by overlapping the sequences of 3′- and 5′-extremities and amplification by reverse transcription PCR. Sequence analysis revealed that the open reading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 47 publications
(49 reference statements)
0
38
0
Order By: Relevance
“…Zhang et al. () showed the MIC5 protein of E. acervulina could be expressed in sporozoite and merozoite stages of the life cycle. In this study, we found that EaMIC3 could be detected in sporozoite stages of the life cycle and was located mainly at the apical tip of the sporozoite.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Zhang et al. () showed the MIC5 protein of E. acervulina could be expressed in sporozoite and merozoite stages of the life cycle. In this study, we found that EaMIC3 could be detected in sporozoite stages of the life cycle and was located mainly at the apical tip of the sporozoite.…”
Section: Discussionmentioning
confidence: 99%
“…() found that EtMIC1 induced significant level of the IFN‐γ and IL‐2 transcript profiles at first immunization, and reached the peak at third immunization, and Zhang et al. () reported that EaMIC5 could provocate high level of the IL‐4 and sCD8. However, in this research, we found that EaMIC3 induced significant level of the IFN‐γ, IL‐10, IL‐17, and TGF‐β at first immunization, and reached the peak at second immunization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After induction with IPTG (Sigma-Aldrich, St Louis, MO), the rTgH4 protein fused to the 109 aa Trx. Tag thioredoxin with a C-terminal His-tag (fusion protein called further in the paper rTgH4) was purified using a Ni 2+ -nitrilotriacetic acid (Ni-NTA) column (GE Healthcare, Madison, WI) based on the company's directions (Zhang et al 2014(Zhang et al , 2016. Then, the pET-32a vector Trx.…”
Section: Molecular Cloning Of Tgh4 and Expression Of Recombinant Tgh4mentioning
confidence: 99%